On the Sensitivity of the Level of Output to Savings: Embodiment and Disembodiment - Levhari, David; Sheshinski, Eytan (Quarterly Journal of Economics, 1967)
Journal Article On the Sensitivity of the Level of Output to Savings: Embodiment and Disembodiment Get access David Levhari, David Levhari The Hebrew University of Jerusalem Search for other works by this author on: Oxford Academic Google Scholar Eytan Sheshinski Eytan Sheshinski Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 81, Issue 3, August 1967, Pages 524–528, https://doi.org/10.2307/1884816 Published: 01 August 1967